Student Learning Difficulties in Terms of the STIF in Framework of Fractional Material - Kamid; Dewi, Rina Kusuma; Kurniawan, Dwi Agus; Azzahra, Miftahul Zannah; Nawahdani, Ahmad Mansur (LPPM Undiksha, 2023)
Learning mathematics is possible because of problems in learning facts, concepts, operations and principles. Students who need help teaching mathematics often make mistakes in counting. This research aims to analyze the difficulties experienced by students in fractional material with the types of intelligent thinking, feeling and sensing in learning mathematics. This research approach uses a qualitative approach to document study and interviews. The sample in this study was fourth-grade elementary school students. The sampling technique used is random sampling. Primary data and secondary data are the source of data in this study. The instrument used is in the form of interview sheets and questions regarding fractional material in mathematics lessons. Data analysis was carried out based on the Miles and Huberman model. Based on the results of the STIFIn test, it was found that the Feeling, Sensing and Thinking students were superior in mastering the concept of fractions to the Instinct and Intuiting students. Furthermore, students' strategies in developing fractional problem-solving strategies are comparing fractions with other simple standard fractions, comparing fractions based on the denominator and quantifier, and making fraction representations in the form of flat structures to understand and compare fractions.